2009
DOI: 10.2106/jbjs.h.00155
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Revision Total Hip Arthroplasty in the United States

Abstract: Hip instability and mechanical loosening are the most common indications for revision total hip arthroplasty in the United States. As further experience is gained with the new diagnosis and procedure codes specifically related to revision total hip arthroplasty, this information will be valuable in directing future research, implant design, and clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
509
1
24

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,529 publications
(542 citation statements)
references
References 13 publications
8
509
1
24
Order By: Relevance
“…The MoM and MoP cohorts were then each independently queried to identify those patients with a subsequent isolated acetabular revision code (ICD-9-CM procedure code 00.71 or CPT 27137). These bearing surface and isolated acetabular revision codes were introduced in 2005 and should be used when the acetabular component is revised whether or not the femoral head is revised [4]. For the specific surgical and medical complications, the cohorts were then filtered to exclude any patient whose isolated acetabular revision occurred in 2011 or 2012 to have at least 2-year followup for these patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MoM and MoP cohorts were then each independently queried to identify those patients with a subsequent isolated acetabular revision code (ICD-9-CM procedure code 00.71 or CPT 27137). These bearing surface and isolated acetabular revision codes were introduced in 2005 and should be used when the acetabular component is revised whether or not the femoral head is revised [4]. For the specific surgical and medical complications, the cohorts were then filtered to exclude any patient whose isolated acetabular revision occurred in 2011 or 2012 to have at least 2-year followup for these patients.…”
Section: Methodsmentioning
confidence: 99%
“…According to one study of the Medicare database, isolated revision of the acetabular component accounted for 13% of all revisions [4]. Isolated acetabular revision can be challenging and is associated with increased complications but has advantages of decreased blood loss and surgical time compared with both-component revisions [28,35,39].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lü bbeke and colleagues showed that unadjusted quality of life and satisfaction were significantly lower after revision (42). Adjustment for patient characteristics revealed that this difference was only partially explained by the greater morbidity and older age of the patients undergoing revision (42 (45). This analysis was carried out by using the US ICD-9-CM databases concerning codes specifically related to revision after THA in a large sample representative of the US population until 2006.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis was carried out by using the US ICD-9-CM databases concerning codes specifically related to revision after THA in a large sample representative of the US population until 2006. The study found that the most common type of revision after a THA procedure was the all-component revision (41.1%), while the most common causes of revision were instability/dislocation (22.5%), mechanical loosening (19.7%), and infection (14.8%) (45). Revision procedures following THA were most commonly performed in large, urban, nonteaching hospitals for Medicare patients in people ages 75-84 years.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dislocation has been reported to be a major reason for revision in THA [4]. In artificial hips, dislocation is almost always caused by the impingement of the femoral stem neck on the acetabular liner.…”
Section: Introductionmentioning
confidence: 99%